Single Cell Protein Analysis Methods and Protocols - Singh, Anup K.; Singh, Anup K.; Chandrasekaran, Aarthi.; Chandrasekaran, Aarthi. (Methods in Molecular Biology, 2015)
This volume highlights recent developments in flow cytometry, affinity assays, imaging, mass spectrometry, microfluidics and other technologies that enable analysis of proteins at the single cell level. The book also includes chapters covering a suite of biochemical and biophysical methods capable of making an entire gamut of proteomic measurements, including analysis of protein abundance or expression, protein interaction networks, post-translational modifications, translocation, and enzymatic activity. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and thorough, Single Cell Protein Analysis: Methods and Protocols is useful to researchers and students in biological and biomedical sciences who have an interest in proteomic measurements in cells.